The Influence Of Organizational Culture On Employee Discipline At The Institute Of Domestic Government (IPDN) Sumedang District - Matiin, Nuuridha; Sampe, Ferdinandus (Decision, 2022)
This research aims to determine the influence of organizational culture on employee discipline at IPDN Sumedang Regency. Based on the research results, it is known that there are problems with employee work discipline, namely disobeying time regulations and disobeying behavioral rules at work. The research method used by researchers is descriptive with a quantitative approach. The number of respondents in this study was 30 people. Data collection techniques were carried out through observation, interviews and questionnaires. The data analysis techniques used consist of validity tests, reliability tests and simple linear regression tests. Based on the results of research and observations made by researchers regarding the influence of organizational culture (X) on employee discipline (Y), it is 0.627 if the percentage is 62.7%. Based on these analyses, the hypothesis that the author proposes is that there is a positive influence between the Organizational Culture variable and the Employee Discipline variable at the Institute of Internal Government (IPDN) Sumedang Regency, which can be accepted and proven to be true. After conducting research by distributing questionnaires, observations and interviews, regarding the Influence of Organizational Culture on Employee Discipline at IPDN Sumedang Regency, the researcher has a suggestion, namely that IPDN needs to implement an organizational culture that always prioritizes discipline, productivity and effectiveness.